2017
DOI: 10.2903/j.efsa.2017.4720
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of glycerol (E 422) as a food additive

Abstract: The ANS Panel provides a scientific opinion re-evaluating the safety of glycerol (E 422) used as a food additive. In 1981, the Scientific Committee on Food (SCF) endorsed the conclusion from the Joint FAO/ WHO Expert Committee on Food Additives (JECFA) in 1976 of 'acceptable daily intake (ADI) for man not specified'. The Panel concluded that glycerol has low acute toxicity and that local irritating effects of glycerol in the gastrointestinal tract reported in some gavage studies was likely due to hygroscopic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 81 publications
0
38
0
Order By: Relevance
“…Glycerol is used in the manufacturing process of mono‐ and di‐glycerides of fatty acids (E 471) and, therefore, the recommendations made by the Panel for the specifications of glycerol (E 422) used as a food additive (EFSA ANS Panel, ) should apply to the EU specifications for E 471.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycerol is used in the manufacturing process of mono‐ and di‐glycerides of fatty acids (E 471) and, therefore, the recommendations made by the Panel for the specifications of glycerol (E 422) used as a food additive (EFSA ANS Panel, ) should apply to the EU specifications for E 471.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the Panel considered that it is very likely that hydrolysis of mono‐ and di‐glycerides of fatty acids by lipases in the gastrointestinal tract would occur, resulting in the release of glycerol and fatty acids. The Panel re‐evaluated glycerol (E 422) and fatty acids (E 570) as food additives and concluded that there was no safety concern regarding their use as food additives (EFSA ANS Panel, ,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Panel recommended that: the European Commission considers lowering the current limits for toxic elements (arsenic, lead, mercury and cadmium) in the EU specifications for PEFA (E 475 in order to ensure that the food additive will not be a significant source of exposure to these toxic elements in food. the European Commission considers revising the EU specifications for PEFA (E 475) including maximum limits for epichlorohydrin and glycidol, given that during the manufacturing processes of polyglycerols these genotoxic impurities could be present. the European Commission considers revising the EU specifications for PEFA (E 475) including maximum limits for trans fatty acids because PEFA (E 475) can be manufactured by glycerolysis of hydrogenated fats and/or oils, which contain significant amounts of trans fatty acids. the European Commission considers revising the EU specifications for PEFA (E 475) including maximum limits for glycidyl esters/glycidol and 3‐monochloropropane‐1,2‐diol (3‐MCPD) esters, because it is likely that residues of those substances occur in the food additive PEFA (E 475), if they were present in the raw materials used in the manufacturing of the food additive by transesterification. the European Commission considers revising the EU specifications for PEFA (E 475) including maximum limits for erucic acid since erucic acid can be present among the fatty acids in edible oils, which can be used for manufacturing of PEFA (E 475). the European Commission considers revising the EU specifications for PEFA (E 475) including maximum limits for impurities currently included in the EU specifications for glycerol (E 422) or recommended by the Panel in the re‐evaluation of glycerol (E 422) (EFSA ANS Panel, ,b,c). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Panel noted that the absorption of intact PEFA before hydrolysis to polyglycerols and fatty acids in the gastrointestinal tract is extremely low. The safety of polyglycerols and specific fatty acids has recently been assessed in the opinions on the re‐evaluation of polyglycerol polyricinoleate (E 476) (EFSA ANS Panel, ) and of fatty acids (E 570) (EFSA ANS Panel, ). No adverse effects of polyglycerols or specific fatty acids were identified in studies reported in those opinions.…”
Section: Discussionmentioning
confidence: 99%